Performance analysis comparison of optical burst switching networks' contention resolution techniques - Abdullah Naji, Laila A. Wahab; Eltahir, Ibrahim Khider; Al-Shargabi, Mohammed; Haider, Adel Sallam (Indonesian Journal of Electrical Engineering and Computer Science, 2022)
Optical burst switching (OBS) is a transporting network for the optical internet in the years ahead vision. As OBS depends on statistical multiplexing, the effect of contention resolution is the main issue to achieve a low probability losing of burst. Basically, there are different ways to resolve contentions in the OBS networks like wavelength conversion, deflection routing, burst segmentation and optical buffering using fiber delay lines. Burst segmentation and deflection routing as well as fiber delay lines technologies, are discussed among the various accessible conflict resolution techniques in this study. However, the main aim of this study is to demonstrate that, the performance of fiber delay line (FDL) is better than other techniques to resolve contention by comparing the performance of these different schemes based on burst losing probabilities and the data handling capability. To evaluate the performance, appropriate mathematical formulae were used. Under the MATLAB environment, the performance was measured based on the probability of burst loss versus incoming traffic (load). The outcomes suggest that deflection routing outperforms fiber delay lines and burst segmentation in the OBS network in terms of resolve the contention.